Teaching Using Adey- Shire Model and its Effect in Achievement and Critical Thinking for first intermediate students in Mathematics (Journal Of Educational and Psychological Researches, 2017)
The aim of this research is to measure the effect of Adey- Shire model in the achievement and critical thinking of first intermediate female students in mathematics. The researcher adopted the experimental method with a post-test, the research of sample consists of (60) female students, divided into two groups with (30) students in the experimental group, that studied with Adey- Shire model, and (30) students in the control group who studied in the usual way. The two groups are equivalent in many variables. The researcher makes two tests of multiple choices, the first one is an achievement test consists (30) items and another test was for a critical thinking test with (25) items. The statistical analysis make to both tests is made with sycometerics proprieties extraction. The result showed that there are statistical differences between the experimental group and the control group in achievement and critical thinking tests for the experimental side.